2023
DOI: 10.3390/ncrna9050058
|View full text |Cite
|
Sign up to set email alerts
|

The Intergenic Type LncRNA (LINC RNA) Faces in Cancer with In Silico Scope and a Directed Lens to LINC00511: A Step toward ncRNA Precision

Shorouk Eldash,
Eman F. Sanad,
Dina Nada
et al.

Abstract: Background: Long intergenic non-coding RNA, is one type of lncRNA, exerting various cellular activities, as does ncRNA, including the regulation of gene expression and chromatin remodeling. The abnormal expression of lincRNAs can induce or suppress carcinogenesis. Main body: LincRNAs can regulate cancer progression through different mechanisms and are considered as potential drug targets. Genetic variations such as single nucleotide polymorphisms (SNPs) in lincRNAs may affect gene expression and messenger ribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 176 publications
0
3
0
Order By: Relevance
“…Recent advances in high-throughput Next-Generation Sequencing (NGS) technologies have led to the discovery of non-coding RNAs (ncRNAs), unveiling novel therapeutic biomarkers in cancer research, particularly in the context of NSCLC. These ncRNAs encompass microRNAs (miRNAs), 7 , 8 long non-coding RNAs (lncRNAs), 9 , 10 and circular RNAs (circRNAs). 11 Notably, while the biological functions of the majority of circRNAs remain unclear, the circRNA–miRNA–mRNA regulatory networks, comprising circRNAs and their downstream miRNAs and target mRNAs, may play a crucial role in cancer initiation and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in high-throughput Next-Generation Sequencing (NGS) technologies have led to the discovery of non-coding RNAs (ncRNAs), unveiling novel therapeutic biomarkers in cancer research, particularly in the context of NSCLC. These ncRNAs encompass microRNAs (miRNAs), 7 , 8 long non-coding RNAs (lncRNAs), 9 , 10 and circular RNAs (circRNAs). 11 Notably, while the biological functions of the majority of circRNAs remain unclear, the circRNA–miRNA–mRNA regulatory networks, comprising circRNAs and their downstream miRNAs and target mRNAs, may play a crucial role in cancer initiation and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies have shown that this could be achieved via epigenetics markers long noncoding RNAs and microRNAs. 19 , 20 In view of the above background, TRP channels play a role in a variety of malignant tumors, and the challenges and urgency posed by the poor efficacy and very poor prognosis of pancreatic adenocarcinoma (PAAD). In order to further fill the lack of studies related to TRP channels in pancreatic cancer, and to find new therapeutic targets and biomarkers to improve the clinical prognosis of pancreatic cancer, we performed genetic and immunological characterization of TRP channels in PAAD, as well as related functional and prognostic analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the potential of the TRP family as viable biomarkers or therapeutic targets for pancreatic cancer remains uncertain. Relevant studies have shown that this could be achieved via epigenetics markers long noncoding RNAs and microRNAs 19,20 . In view of the above background, TRP channels play a role in a variety of malignant tumors, and the challenges and urgency posed by the poor efficacy and very poor prognosis of pancreatic adenocarcinoma (PAAD).…”
Section: Introductionmentioning
confidence: 99%